Coacervate‐Derived Hydrogel with Effective Water Repulsion and Robust Underwater Bioadhesion Promotes Wound Healing. Issue 31 (15th September 2022) - Peng, Xin; Li, Yuan; Li, Tianjie; Li, Yucong; Deng, Yingrui; Xie, Xian; Wang, Yi; Li, Gang; Bian, Liming
Abstract: Achieving robust underwater adhesion by bioadhesives remains a challenge due to interfacial water. Herein a coacervate‐to‐hydrogel strategy to enhance interfacial water repulsion and bulk adhesion of bioadhesives is reported. The polyethyleneimine/thioctic acid (PEI/TA) coacervate is deposited onto underwater substrates, which can effectively repel interfacial water and completely spread into substrate surface irregularities due to its liquid and water‐immiscible nature. The physical interactions between coacervate and substrate can further enhance interfacial adhesion. Furthermore, driven by the spontaneous hydrophobic aggregation of TA molecules and strong electrostatic interaction between PEI and TA, the coacervate can turn into a hydrogel in situ within minutes without additional stimuli to develop enhanced matrix cohesion and robust bulk adhesion on diverse underwater substrates. Molecular dynamics simulations further reveal atomistic details of the formation and wet adhesion of the PEI/TA coacervate via multimode physical interactions. Lastly, it is demonstrated that the PEI/TA coacervate‐derived hydrogel can effectively repel blood and therefore efficiently deliver the carried growth factors at wound sites, thereby enhancing wound healing in an animal model. The advantages of the PEI/TA coacervate‐derived hydrogel including body fluid‐immiscibility, strong underwater adhesion, adaptability to fit irregular target sites, and excellent biocompatibility make it a promising bioadhesive for diverse biomedical applications. Abstract : Coacervate deposited onto underwater or wet substrates can effectively repel interfacial water and completely spread into substrate surface irregularities, resulting in tight contact and interfacial adhesion, due to its liquid and water‐immiscible nature. Then, driven by the spontaneous hydrophobic aggregation, coacervate can turn into a hydrogel in situ without additional stimuli to develop enhanced matrix cohesion and robust bulk adhesion.